THE EFFECT OF ELECTRONIC WORD OF MOUTH ON PURCHASE INTEREST BASED ON SHOPPING EXPERIENCE - Monique Mega Mahardhika; Catharina Badra Nawangpalupi; Gandhi Pawitan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study discusses the relationship between Electronic Word of Mouth (EWOM) and consumer purchase interest for an online shop in fashion. The study involved 100 respondents from the Instagram account followers, including 50 people who had made a purchase and 50 others who had never made a purchase. The finding shows a positive relationship between the shopping experience and the influence of EWOM, although the correlation rate is low. The shopping experience has a positive and strong magnitude on the effect to the EWOM on purchase intention. The odds ratio shows that the shopping experience affects the ease of online purchases. Also, there is an influence on the shopping experience with purchase interest which is influenced by EWOM.